AI in Special Education: Enhancing Learning Outcomes for Students with Disabilities - Khan, Reshma; Sujatha, S. (International Journal of Accounting and Economics Studies, 2025)
Integration of Artificial Intelligence (AI) in education has opened different avenues for addressing challenges faced by special children. AI technologies like virtual facilitation, voice-to-text systems and adaptive learning tools offer a more personalised solution which further helps in overcoming the sensory and cognitive barrier in the traditional educational system. However, its implementation dynamic has faced different challenges, like societal stigma, infrastructural deficits, lack of teacher training and ethical biases mainly in developing countries such as India. This study employs a primary quantitative research methodology, drawing insights from a survey of 101 participants to assess in the AI effectiveness in special education. The research explores the supervised learning algorithms that drive these technologies and enhance inclusivity and accessibility as well. The findings emphasise are capable of enhancing teaching ability, helping to aid the educational needs of special education. AI has the potential to revolutionise Indian special children’s learning outcomes through creating an accessible and inclusive educational landscape. Additionally, the research explores the economical value of AI technologies in special education with respect to their projected economic benefits concerning the minimization of dependency on professional staff, costly assistive devices, and other specialized resources.